(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Foliar application of B and Zn fertilizer solutions was evaluated for the management of blast of rice disease under natural condition in the field. Three times fertilizer solutions were sprayed on the foliage of rice plants cv. BRRI dhan49 to examine their influence on the growth parameters, yield parameters, and incidence of blast disease. Characteristics leaf blast symptoms appeared both in control and treated plants at 60 DAT. The blast incidence increased with time and recorded the highest at 120 DAT. Foliar spraying of B and Zn fertilizer significantly increased all growth and yield parameters and reduced disease parameters at all stages of plant growth. All combinations of B and Zn fertilizer solutions sprayed on the foliage slowed down the blast incidence at all growth stages of rice plant. At panicle initiation stage (60 DAT) 71.65% and 75.69 % incidence was reduced in T5 (Foliar application of Zn fertilizer @5 kg/ha) and T6 (Foliar application of B and Zn fertilizer @ 2 kg/ha and 4 kg/ha) compared to untreated control. At flowering stage (90 DAT) 83.48 % and 86.65 % reduction in disease incidence was found in T6 (Foliar application of B and Zn fertilizer @ 2 kg/ha and 4 kg/ha) and T7 (Foliar application of B and Zn fertilizer @ 3 kg/ha and 5 kg/ha). At 120 DAT, 80.31% and79.94 % reduction was found in T6 (Foliar application of B and Zn fertilizer @ 2 kg/ha and 4 kg/ha) and T7 (Foliar application of B and Zn fertilizer @ 3 kg/ha and 5 kg/ha). A significant increase (21.00 % over control) in total no. grain/ panicle was found in T6. Foliar spraying of B and Zn fertilizer solution is proved to be effective either @ 2 and 4 kg/ha (T6) or @ 3 and 5 Kg/ha (T7) on the foliage is effective considering lower blast disease incidence as well as total hill/plot, no. of infected hill/plot, no. of tillers/hill, no. of infected tiller/hill, total panicle/hill, no. of infected panicle/hill and total grain/panicle. J Bangladesh Agril Univ 18(3): 571–577, 2020 https://doi.org/10.5455/JBAU.114039